1995
DOI: 10.1111/j.1365-2478.1995.tb00128.x
|View full text |Cite
|
Sign up to set email alerts
|

A joint inversion algorithm to process geoelectric and sutface wave seismic data. Part I: basic ideas1

Abstract: For the exploration of near-surface structures, seismic and geoelectric methods are often applied. Usually, these two types of method give, independently of each other, a sufficiently exact model of the geological structure. However, sometimes the inversion of the seismic or geoelectric data fails.These failures can be avoided by combining various methods in one joint inversion which feads to much better parameter estimations of the model than the independent inversions.A suitable seismic method for exploring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
61
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 20 publications
0
61
0
Order By: Relevance
“…Manglik and Verma (1999) included DC resistivity inversion to their joint MT -seismic inversion algorithm. Hering et al (1995) reported an example of combining DC electrical data with surface wave data. Recently, Gallardo and Meju (2007) presented an algorithm for the joint inversion of MT and seismic refraction data for two dimensional structures.…”
Section: Introductionmentioning
confidence: 98%
“…Manglik and Verma (1999) included DC resistivity inversion to their joint MT -seismic inversion algorithm. Hering et al (1995) reported an example of combining DC electrical data with surface wave data. Recently, Gallardo and Meju (2007) presented an algorithm for the joint inversion of MT and seismic refraction data for two dimensional structures.…”
Section: Introductionmentioning
confidence: 98%
“…Among the first geoelectric studies in this field were published by Gyulai (1989) and by Noel and Xu (1991). Noel and Xu (1991) carried out two-dimensional parameter sensitivity studies for geoelectric tomography; Hering et al (1995) carried out 1D parameter sensitivity studies with the Schlumberger, radial (axial) dipole and two-electrode arrays, in order to reveal their potential in various (geoelectric and seismic-geoelectric) joint inversions; Gyulai (1995) discussed parameter sensitivity of two-electrode, three-electrode, Wenner-, Sclumberger-and radial-dipole arrays in case of inclined layered models; Gyulai (1998) calculated parameter sensitivities in case of several arrays in investigation of subsurface holes. As a practical example of parameter sensitivity studies, Nyári and Kanli (2007) studied effect of small 3D inhomogeneities on 2D interpretation carried out with various arrays.…”
Section: Introductionmentioning
confidence: 99%
“…Sena and Toksöz (1990) used high-frequency EM data to derive subsurface electrical conductivity and permittivity, and Zhang and Oldenburg (1999) used EM data to map magnetic susceptibility and electrical conductivity simultaneously. Hering et al (1995) showed that improved results may be obtained through joint inversion if multitudes of data are available. For the resistivity problem Schlumberger, radial-dipole and two-electrode sounding data were jointly used to improve resistivity imaging, and for the seismic problem Love and Rayleigh group slowness data were used to obtain improved near-surface velocity structures.…”
Section: Introductionmentioning
confidence: 99%